Biogenic volatile organic compounds in different ecosystems in Southern Kenya. (1st February 2021) - Liu, Yang; Schallhart, Simon; Tykkä, Toni; Räsänen, Matti; Merbold, Lutz; Hellén, Heidi; Pellikka, Petri
Abstract: Biogenic volatile organic compounds (BVOCs) have an important impact on atmospheric chemistry. Mixing ratio of BVOCs in different ecosystems have been measured and discussed in detail in recent decades. However, field measurements from tropical Africa remain scarce. In this study, we present the mixing ratio of BVOCs, including isoprene, monoterpenoids, sesquiterpenes, bornylacetate, and 2–methyl–3–buten–2–ol from typical forests, bushlands, grasslands and agricultural ecosystems in Taita Taveta County, southern Kenya. The measurements were conducted in April 2019 during the end of the dry season. The total BVOC mixing ratios in forest, agricultural, bushland and grassland ecosystems were 913 ± 183 pptv, 1094 ± 179 pptv, 751 ± 47 pptv and 886 ± 95 pptv, respectively. Isoprene represented 76%, 86%, 91% and 85%, respectively, of total mixing ratios. Monoterpenoids represented in 23%, 14%, 8% and 14% of total mixing ratios, respectively. Monoterpenoid have strong effect on the total BVOC mixing ratios, especially at the certain landscape (i.e. wattletree, pine and cypress forest, and dry grassland). The monoterpenoids were dominated by α–pinene, limonene and β–pinene in all of the ecosystems. Linalool was found in a relative high mixing ratio from all lowland samples, which was likely responding to the lower soil moisture. Highlights: BVOC mixing ratios from forest and agricultural ecosystem were higher than from bushland and grassland in Kenya. Monoterpenoids have strong effect on the total BVOC mixing ratios at wattletree, pine, cypress forest, and dry grassland. α–pinene, limonene, and β–pinene lead the total mixing ratios of monoterpenoid.